2001
DOI: 10.1897/1551-5028(2001)020<1012:motpah>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the Polycyclic Aromatic Hydrocarbon Fluoranthene by the Polychaete Capitella Capitata Species I

Abstract: Previous studies have shown that infaunal deposit feeders may enhance the loss of organic contaminants from sediments. However, the extent to which this occurs as a result of sediment microbial stimulation, porewater flushing, or biotransformation by infauna remains unclear. The purpose of this study was to determine whether the infaunal polychaete Capitella sp. I is able to metabolize the polycyclic aromatic hydrocarbon (PAH) fluoranthene and to provide an initial characterization of the metabolites produced.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Presented at the 23rd Annual Meeting, Society of Environmental Toxicology and Chemistry, Salt Lake City, Utah, USA November 16-20, 2002. olites most likely occurs through a combination of active elimination (e.g., excretion of water soluble conjugates) and passive elimination (e.g., parent PAH and some metabolites) [3,[12][13][14][15]. The little data that exist suggest that invertebrates tend to excrete metabolites more slowly than vertebrate species [6,11,16,17] Current results are conflicting on the degree to which PAH metabolism is inducible in marine invertebrates [3].…”
Section: Introductionmentioning
confidence: 99%
“…Presented at the 23rd Annual Meeting, Society of Environmental Toxicology and Chemistry, Salt Lake City, Utah, USA November 16-20, 2002. olites most likely occurs through a combination of active elimination (e.g., excretion of water soluble conjugates) and passive elimination (e.g., parent PAH and some metabolites) [3,[12][13][14][15]. The little data that exist suggest that invertebrates tend to excrete metabolites more slowly than vertebrate species [6,11,16,17] Current results are conflicting on the degree to which PAH metabolism is inducible in marine invertebrates [3].…”
Section: Introductionmentioning
confidence: 99%
“…The 2,3‐diol Flu was produced via biotransformation of Flu by liver postmitochondrial supernatant from aroclor‐treated rats, and the same studies showed that 2,3‐diol Flu and 7,8‐diol Flu, of which the latter Flu‐diol was mutagenic only in high concentrations, could be metabolized further in the presence of postmitochondrial supernatant to more active mutagens [2,34]. Forbes et al [17] found more than 30 different metabolites produced from Flu by Capitella sp. I but unfortunately were unable to identify any of them conclusively.…”
Section: Discussionmentioning
confidence: 99%
“…I. Furthermore, Forbes et al [17] detected a large number of Flu metabolites produced by Capitella sp. I, but their identities were not determined.…”
Section: Introductionmentioning
confidence: 99%
“…Forbes et al (1996) exposed this species to fluoranthene and found that it quickly took up the pollutant in a concentration dependent manner but body levels were undetectable after three days of exposure. This species is able to convert fluoranthene to more hydrophilic substances which are less toxic allowing its existence in heavily polluted sites (Forbes et al 2001) but making it a poor candidate as an indicator species for hydrocarbon pollution. Rust et al (2004) exposed six species of polychaetes to high BaP levels and found that N. succinea and N. virens seemed to be able to convert this PAH to less toxic metabolites most effectively while the maldanid Clymenella torquata was least effective leading them to warn against the use of N. virens as an indicator species for PAH contamination.…”
Section: Polychaetes As Indicators Of Organic Contaminantsmentioning
confidence: 99%